2015
DOI: 10.6004/jadpro.2015.6.3.8
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Calcium and Magnesium to Prevent Neurotoxicity in Patients Receiving Oxaliplatin

Abstract: groundbreaking oral abstract was presented by Charles Loprinzi at the 2013 annual meeting of the American Society of Clinical Oncology (ASCO), addressing the controversial issue of using magnesium and cal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Acupuncture has been anecdotally shown to be effective for neuropathy caused by other chemotherapies, but this has not been studied extensively (33,34). Despite conflicting results from small retrospective studies, calcium and magnesium infusions have been shown, in a phase III randomized study, to have no significant effect in reducing OIN (35,36). While duloxetine, a serotonin and norepinephrine reuptake inhibitor (SNRI), has been shown to be effective in reducing pain for patients with painful chemotherapy-induced neuropathy, its effect in non-painful neuropathy is not well characterized (37).…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has been anecdotally shown to be effective for neuropathy caused by other chemotherapies, but this has not been studied extensively (33,34). Despite conflicting results from small retrospective studies, calcium and magnesium infusions have been shown, in a phase III randomized study, to have no significant effect in reducing OIN (35,36). While duloxetine, a serotonin and norepinephrine reuptake inhibitor (SNRI), has been shown to be effective in reducing pain for patients with painful chemotherapy-induced neuropathy, its effect in non-painful neuropathy is not well characterized (37).…”
Section: Discussionmentioning
confidence: 99%